2015
DOI: 10.5505/phd.2015.47955
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Faculty Members Regarding Mental Illnesses and Patients

Abstract: ÖZETAmaç: Öğretim elemanlarının ruhsal hastalıklara ve hastalara ilişkin tutum ve davranışlarının incelenmesi amacıyla tanımlayıcı olarak yapılmıştır. Bulgular: Araştırmaya katılan öğretim elemanlarının %68.7'si 35-50 yaş grubunda, %56.7'si erkek, %93.7'si şehirde yaşamakta ve %54.3'ü 10-20 yıldır çalışmaktadır. Tanıdığı kişiler arasında ruhsal hastalığı olan öğretim elemanları ruhsal hastalara karşı koruyucu ve insancıl yaklaşıma sahiptir. Erkek öğretim elemanları ruhsal hastalıkların ço-cukluk çağındaki bozu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
3
1
Order By: Relevance
“…It has been observed that there is a positive and significant relationship between the negative attitude towards individuals with mental problems and the level of professional burnout in nurses working in psychiatric hospitals (7). Yuksel et al found that lecturers who knew someone with a mental illness had a more protective and humanistic approach towards these patients (9). In the present study, mental health ideology and goodwill scores of PCG branch teachers were lower than those of preschool and classroom teaching branches.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…It has been observed that there is a positive and significant relationship between the negative attitude towards individuals with mental problems and the level of professional burnout in nurses working in psychiatric hospitals (7). Yuksel et al found that lecturers who knew someone with a mental illness had a more protective and humanistic approach towards these patients (9). In the present study, mental health ideology and goodwill scores of PCG branch teachers were lower than those of preschool and classroom teaching branches.…”
Section: Discussioncontrasting
confidence: 50%
“…In this study, as age and time spent in the profession increased, the score of goodwill towards individuals with mental problems increased, and the scores of fears of individuals and exclusion decreased. On the contrary, in the study of Yuksel et al, lecturer's attitudes towards psychiatric patients did not change with their age and time spent in the profession (9). Again, it is stated in other studies that elderly individuals believe that people with mental health problems are more aggressive, less intelligent than other people and that they should be socially restricted (22,23).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations